Histone deacetylase inhibitors sodium butyrate and valproic acid delay spontaneous cell death in purified rat retinal ganglion cells - Biermann, Julia (Molecular Vision, 2011)
PURPOSE: Histone deacetylase inhibitors (HDACi) have neuroprotective effects under various neurodegenerative conditions, e.g., after optic nerve crush (ONC). HDACi-mediated protection of central neurons by increased histone acetylation has not previously been demonstrated in rat retinal ganglion cells (RGCs), although epigenetic changes were shown to be associated with cell death after ONC. We investigated whether HDACi can delay spontaneous cell death in purified rat RGCs and analyzed concomitant histone acetylation levels. METHODS: RGCs were purified from newborn (postnatal day [P] 0–P2) rat retinas by immunopanning with antibodies against Thy-1.1 and culturing in serum-free medium for 2 days. RGCs were treated with HDACi, each at several different concentrations: 0.1–10 mM sodium butyrate (SB), 0.1–2 mM valproic acid (VPA), or 0.5–10 nM trichostatin A (TSA). Negative controls were incubated in media alone, while positive controls were incubated in 0.05–0.4 IU/µl erythropoietin. Survival was quantified by counting viable cells using phase-contrast microscopy. The expression of acetylated histone proteins (AcH) 3 and 4 was analyzed in RGCs by immunohistochemistry. RESULTS: SB and VPA enhanced RGC survival in culture, with both showing a maximum effect at 0.1 mM (increase in survival to 188% and 163%, respectively). Their neuroprotective effect was comparable to that of erythropoietin at 0.05 IU/µl. TSA 0.5–1.0 nM showed no effect on RGC survival, and concentrations ≥5 nM increased RGC death. AcH3 and AcH4 levels were only significantly increased in RGCs treated with 0.1 mM SB. VPA 0.1 mM produced only a slight effect on histone acetylation. CONCLUSIONS: Millimolar concentrations of SB and VPA delayed spontaneous cell death in purified RGCs; however, significantly increased histone acetylation levels were only detectable in RGCs after SB treatment. As the potent HDACi TSA was not neuroprotective, mechanisms other than histone acetylation may be the basis on which SB and VPA are acting in this model. Additional studies are necessary to identify HDACi-targeted genes and pathways involved in RGC protection.